Analisis Kadar Fe pada Lemiding Tua dan Muda di Wilayah Kubu Raya Kalimantan Barat - Gervacia Jenny Ratnawati; Ratih Indrawati (Health Information : Jurnal Penelitian, 2019)
Lemiding (Stenochlaena Palustris) is one type of vegetable that grows on peatland, which is a type of fern or fern that is included in the kingdom of plantae and the pteridophyta division (ferns) which is commonly found in the forests of Kalimantan, especially West Kalimantan. Lemiding is one that is easy and fast to adapt to nature, so that it can grow anywhere such as on tree trunks, rotten wood or dry land, even though this local vegetable will flourish on peatlands because of the considerable water intensity facilitate breeding. In the region of West Kalimantan, Lemiding plants are usually consumed in two types, namely young lemiding (white) and old lemiding (red). Red lemiding is a green lemiding with a reddish color, while white lemiding is a green lemiding with a pale color. Lemiding in the people of Kalimantan is processed into vegetables or added as the main vegetable in the typical foods of West Kalimantan, namely spicy porridge. This study aims to determine the comparison of Fe levels in young and old Stenochlaena Palustris in the Kubu Raya Regency. The inspection methodology that will be used is using Atomic Absorption Spectrophotometer (AAS). Based on the results of the study obtained an average Fe content in young lemiding is 0.39 mg / L and old lemiding is 0.48 mg / L. Statistical test results obtained by computerized data processing throughtest Mann Whitney U obtained p value of 0.038, p <0.05, so it can be concluded that Ha is accepted which means that there are differences in Fe levels in young lemids and old lemiding.